Evaluación del sistema de manejo de residuos sólidos en la ciudad de Santo Domingo – 2008 - Cordova Lima, David (2009)
The present investigation I am carried out in the locality of Santo Domingo, located in the district homónimo, province of Morropon, department of Piura. Santo Domingo is a small city categorizada like "Villa", who comprises of the Piurana mountain range, located in the left margin of the anto Domingo river. His geographical cordinateses according to the National Geophysical Institute of Peru, are 79° 52' 27" West Longitude and 05º 01'39' south latitude of the meridian of Greenwich of the runner Andean Power Station, located to 1475 m.s.n.m. and distant 130 km by highway of the city of Piura. The thesis document has been structured contemplating the following aspects: accomplishment of the diagnosis of the present situation of the handing of solid remainders, considering operative and administrative the part. In this types of studies it is seen concerning the characterization is solid remainders, with which it has been determined the PPC, density, physical composition of the solid remainders and finally with humidity analysis. The system of integral handing of solid remainders has been designed in such a way that it includes/understands the harvesting stages, it transports, treatment (for this aim has been chosen by the design of a plant of production of compost) and final disposition, considering for this stage the design of the manual sanitary filling, using method of the area. . For the construction of the sanitary filling the land has been evaluated whereupon it counts municipality like place of final disposition. For the project of generation of solid remainders the election has been made of method of population projection that adapts itself to the growth of the population. Next the aspect is approached gerenciamiento in which the creation sets out of the unit of public cleaning unit for such aim the points for his settle down operation, has determined the tariff by concept of cleaning on the basic of the system of integral handing of solid remainders.